RESEARCH ON COOPERATIVE LEARNING BASED ON＂ FLIPPED CLASSROOM" TEACHING MODE IN HIGHER VOCATIONAL ENGLISH TEACHING - Shuhui, Tan (PEOPLE: International Journal of Social Sciences, 2016)
Since its appearance, the teaching mode "flipped classroom" has quickly become a most popular teaching mode in recent years. In practice, many a scholar has tried exploring this teaching mode and has got remarkable effectiveness. According to the characteristics of "flipped classroom" teaching mode and its realization form, this paper mainly explores the feasibility of applying "flipped classroom" and analyzes the implementation strategies of cooperative learning in higher vocational English teaching.